TEPUNG RUMPUT LAUT MENURUNKAN KADAR LDL (LOW DENSITY LIPOPROTEIN) PLASMA TIKUS WISTAR HIPERKOLESTEROLEMIA - Julyasih, K. Sri Marhaeni (REKAPANGAN, 2012)
In Bali  there  are  several types  of  seaweed  that  is  often  consumed  as  a  vegetable,  such  as Caulerpa  spp.  (local  name  Bulung  Boni),  Gracillaria  spp  (local  name  Bulung  Sangu)  and  Euchema spinosum,  its  potential effect in  lowering  blood  cholesterol  levels,    therefore  it  is  necessary    to determine of  plasma low  density  lipoprotein  (LDL)  cholesterol  level  of  Wistar  rat  after  treated Caulerpa  spp,  Gracillaria  spp. and  Euchema  spinosum. This  experimental  study  used  completely  randomized design Research using using a total of 32 Wistar rats divided into eight sample groups. The  eight  sample  groups  were  respectively  designated  as  negative  control  group,  positive  control group, and six  treated sample groups, respectively fed orally with a dose of 1 g and 1,5 g seaweed powder  of Caulepa  spp.  1g  and  1,5  g  powder of Gracilaria  spp.,  and  1  g  and  1,5  g  Euchema spinosum   per  100g  body  weight  per  day.  Each  treatment  was  repeated  four  times.  Our  study showed  that  rat fed  with  high  cholesterol  diet and  treated  Caulerpa  spp.,  Gracilaria  spp., and E.spinosum with a dose of 1 g and 1.5 g/100 g body weight rat / day were associated with statistically significantly  lowered  plasma LDL  level  (p  <0.05)  as  compared  with  those   of rats fed  with high-cholesterol diet without treatment with Caulerpa spp., Gracilaria spp., and E.spinosum.Keywords : Caulerpa spp., Gracilaria spp.,  E.spinosum, LDL,  hyperholesterolemic